Analisis Kemampuan Membaca Permulaan Kelas III di SDN Pedesaan dan Perkotaan - Liulinnuha, Liulinnuha; Zainuddin, Almuntaqo (Universitas Nahdlatul Ulama Blitar, 2024)
Reading at the beginning of elementary education is an important stage in the learning process of early grade students. This reading ability is an essential basis for developing more complex literacy skills in the future. The aim of this research is to analyze the comparison of two elementary schools in improving students' reading skills located in villages and urban areas, then the obstacles/difficulties experienced by students in understanding reading. This research is descriptive qualitative research with a case study approach. Data collection techniques used interviews, EGRA tests, and observation. Based on the research results, it shows that reading ability in rural SDNs is lower than in urban SDNs. Difficulties experienced by elementary school students in rural and urban areas include; 1) difficulty reading vowels 2) reading words that have no meaning, 3) difficulty reading a sentence, 4) difficulty remembering words that have been spelled. Based on reading ability, there are 2 Factors, namely inhibiting factors and supporting factors. Supporting factors include; 1) interest in reading, 2) motivation, and 3) learning methods and media. Meanwhile, inhibiting factors are physiological factors and family factors.